Bloodletting & miraculous cures - Lam, Vincent (Weinstein Books, 2007)
Twelve interwoven stories follow the lives of a group of young doctors as they make their way from medical school to the world of emergency rooms, evacuation missions, and research into new viruses, dealing with challenges and moral dilemmas along the way.